Radiation absorption noise for molecular information transfer - Singh, S. Pratap; Singh, Shekhar; Guo, Weisi; Mishra, Saket; Kumar, Sanjay (IEEE, 2020)
Molecular signaling is ubiquitous across scales in nature and finds useful applications in precision medicine and heavy industry. Characterizing noise in communication systems is essential to understanding its information capacity. To date, research in molecular nano communication (MNC) primarily considers the molecular dynamics within the medium, where various forms of stochastic effects generate noise. However, in many real-world scenarios, external effects can also influence molecular dynamics and cause noise. Here, the noise due to the temperature fluctuations from incident electromagnetic (EM) radiation is considered, with applications ranging from cell signaling to chemical engineering. EM radiation and subsequent molecular absorption cause temperature fluctuations which affect molecular dynamics and can be considered as an exogenous noise source for MNC. In this paper, the probability density function of the radiation absorption noise (RAN) is analyzed and to demonstrate applicability, we include characteristics of different tissues of the human body. Furthermore, the closed-form expression of error probability (EP) for MNC under the radiation noise is derived. Numerical analysis is demonstrated on different tissues of the human body: skin, brain, and blood, as well as the polarization factor of incident EM radiation is demonstrated. The coupling relationship between the radiation frequency and the intrinsic impedance of the human body on the PDF of radiation absorption noise is presented. This is useful for understanding how mutual information changes with external radiation sources
Keywords: channel modeling; noise modeling; Molecular communication